Loss of GATA‐1 full length as a cause of Diamond–Blackfan anemia phenotype. Issue 7 (22nd January 2014) - Parrella, Sara; Aspesi, Anna; Quarello, Paola; Garelli, Emanuela; Pavesi, Elisa; Carando, Adriana; Nardi, Margherita; Ellis, Steven R.; Ramenghi, Ugo; Dianzani, Irma
<x xml:space="preserve">Abstract</x> Mutations in the hematopoietic transcription factor GATA‐1 alter the proliferation/differentiation of hemopoietic progenitors. Mutations in exon 2 interfere with the synthesis of the full‐length isoform of GATA‐1 and lead to the production of a shortened isoform, GATA‐1s. These mutations have been found in patients with Diamond–Blackfan anemia (DBA), a congenital erythroid aplasia typically caused by mutations in genes encoding ribosomal proteins. We sequenced GATA‐1 in 23 patients that were negative for mutations in the most frequently mutated DBA genes. One patient showed a c.2T > C mutation in the initiation codon leading to the loss of the full‐length GATA‐1 isoform. Pediatr Blood Cancer 2014;61:1319–1321. © 2014 Wiley Periodicals, Inc.